Exploring how an entrepreneur financially plans for retirement income: Evidence from Thailand - Chavis Ketkaew; Martine Van Wouwe; Preecha Vichitthammaros (Cogent Business & Management, 2019)
Little attention has been paid to an issue of entrepreneurial retirement planning. The purpose of this research paper is to investigate the relationship between entrepreneurial financial attainment capacity and expected retirement income. More explicitly, the following research questions were proposed. 1) What factors determine entrepreneurial financial attainment capacity? 2) What influences anticipated net income after retirement? And 3) how entrepreneurial financial attainment capacity and anticipated net income after retirement are related? Both direct and online questionnaires were used to obtain data from 240 entrepreneurs from different geographical areas in Thailand. Structural Equation Modeling (SEM) was utilized to test the hypothesized relationships among various financial variables. The SEM analyses revealed that entrepreneurial financial attainment capacity positively influence targeted retirement income. Moreover, the results demonstrated that entrepreneurial financial attainment capacity was positively determined by an entrepreneur's investment in financial asset, employment income, business net worth, business income and negatively determined by personal annual expenses and business expenses. On one hand, the research findings indicated that targeted retirement income was positively determined by expected earnings after retirement but negatively elucidated by expected spending after retirement. These results validated and expanded the previous research on entrepreneurial activities and financial planning.
Keywords: 650; Retirement; entrepreneur; Thailand; financial planning